The Analysis of Mental and Physical Structure of Dawn Poetry: “Time Celebrated Rooster’s Crowing” - Herman Wijaya; Lalu Mas’ud; Moh. Irfan (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this study is to describe the inner and physical structure of the poem "Fajr: Time Celebrated by Chicken crowing" by Ahmad Nasrullah using structural studies. This poem is thick with social, moral, and religious values that need to be understood and implemented in everyday life. The method used in this study uses descriptive qualitative. The data source used is every diction which contains structural and mental elements and physical poem "Dawn: Time Celebrated Chicken crowing". Data collection techniques used are library studies with interactive analysis techniques,  which include data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the analysis of the poem entitled "Fajr: Time Celebrated by Chicken crowing" it was found that the inner element was the theme of excess dawn time. The poet is concerned about those who do not take advantage of the dawn, while the message is to make good use of the dawn time. Then, the physical element of the poem is the choice diction which is to make good use of the dawn time. Then, the physical element of the poem is the choice diction which is able to tag the reader. The imagery contained in the poem is the image of motion, temperature, vision, while the majes found are personification and hyperbole with rhythm and rhythm in the form of internal sound patterns that are elements of repetition and equality of sound, be it consonants or vowels. In addition, the typography used is modern poetry.